# Equivalence of Definitions of Normal Subset/3 iff 4

## Theorem

Let $\struct {G,\circ}$ be a group.

Let $S \subseteq G$.

Then:

$S$ is a normal subset of $G$ by Definition 3
$S$ is a normal subset of $G$ by Definition 4.

That is, the following conditions are equivalent:

$(1) \quad \forall g \in G: g \circ S \circ g^{-1} \subseteq S$
$(2) \quad \forall g \in G: g^{-1} \circ S \circ g \subseteq S$
$(3) \quad \forall g \in G: S \subseteq g \circ S \circ g^{-1}$
$(4) \quad \forall g \in G: S \subseteq g^{-1} \circ S \circ g$

## Proof

First note that:

$(5): \quad \paren {\forall g \in G: g \circ S \circ g^{-1} \subseteq S} \iff \paren {\forall g \in G: g^{-1} \circ S \circ g \subseteq S}$
$(6): \quad \paren {\forall g \in G: S \subseteq g \circ S \circ g^{-1}} \iff \paren {\forall g \in G: S \subseteq g^{-1} \circ S \circ g}$

which is shown by, for example, setting $h := g^{-1}$ and substituting.

Therefore:

conditions $(1)$ and $(2)$ are equivalent

and:

conditions $(3)$ and $(4)$ are equivalent.

It remains to be shown that condition $(1)$ is equivalent to condition $(3)$.

Suppose that $(1)$ holds.

Then:

 $\ds \forall g \in G: \,$ $\ds g \circ S \circ g^{-1}$ $\subseteq$ $\ds S$ $\ds \leadsto \ \$ $\ds g^{-1} \circ \paren {g \circ S \circ g^{-1} }$ $\subseteq$ $\ds g^{-1} \circ S$ Subset Relation is Compatible with Subset Product/Corollary 2 $\ds \leadsto \ \$ $\ds S \circ g^{-1}$ $\subseteq$ $\ds g^{-1} \circ S$ Subset Product within Semigroup is Associative/Corollary and the definition of inverse $\ds \leadsto \ \$ $\ds \paren {S \circ g^{-1} } \circ g$ $\subseteq$ $\ds \paren { g^{-1} \circ S} \circ g$ Subset Relation is Compatible with Subset Product/Corollary 2 $\ds \leadsto \ \$ $\ds S$ $\subseteq$ $\ds g^{-1} \circ S \circ g$ Subset Product within Semigroup is Associative/Corollary and the definition of inverse

Thus condition $(1)$ implies condition $(3)$.

The exact same argument, substituting $\supseteq$ for $\subseteq$ and using Superset Relation is Compatible with Subset Product instead of Subset Relation is Compatible with Subset Product proves that $(3)$ implies $(1)$.

$\blacksquare$